2008
DOI: 10.1249/mss.0b013e3181801d40
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise Training Intensity on Abdominal Visceral Fat and Body Composition

Abstract: The metabolic syndrome is a complex clustering of metabolic defects associated with physical inactivity, abdominal adiposity, and aging. Purpose To examine the effects of exercise training intensity on abdominal visceral fat (AVF) and body composition in obese women with the metabolic syndrome. Methods Twenty-seven middle-aged, obese women (mean ± SD; age: 51 ± 9 years and body mass index: 34 ± 6 kg/m2) with the metabolic syndrome completed one-of-three 16-week aerobic exercise interventions: (i) No Exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
250
4
40

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(308 citation statements)
references
References 46 publications
14
250
4
40
Order By: Relevance
“…High-intensity exercise training has been shown to reduce IFA to a greater extent than low-intensity exercise, although it carries identical energy costs (33). The results of our study support this hypothesis, as changes in DBP correlated with DMVPA, DLPA and DMPA.…”
Section: Discussionsupporting
confidence: 81%
“…High-intensity exercise training has been shown to reduce IFA to a greater extent than low-intensity exercise, although it carries identical energy costs (33). The results of our study support this hypothesis, as changes in DBP correlated with DMVPA, DLPA and DMPA.…”
Section: Discussionsupporting
confidence: 81%
“…This could have been induced by training, which is known generally to decrease body fat levels. 23 This greater weight loss in trained mice was also associated with muscular atrophy, as TT Tx animals displayed further muscle atrophy than the untrained animals (as seen with soleus and EDL lower muscle CSA values). This may perhaps be taken as preliminary signs of overtraining or other stress-related factors.…”
mentioning
confidence: 94%
“…[7] Gutin et al [20] reported no clear effect of the intensity of physical training on the reduction of visceral adiposity whereas Irving et al [21] reported the importance of exercise intensity in obese adults with abdominal visceral fat as a primary outcome parameter. On the other hand, Keating et al [22] reported a significant reduction in visceral adipose tissue in overweight/obese adults received different intensity aerobic exercise without differences between the intensity.…”
Section: Discussionmentioning
confidence: 99%
“…[6] The direct relationship between the exercise intensity and a decrease in the visceral fat has not been searched as a primary target widely. [7] Among few studies, some authors [8] reported a significant reduction in visceral adipose tissue without differences between the aerobic exercise intensity, suggesting no precious effect of the intensity, whereas the others [9] reported the importance of aerobic exercise intensity in abdominal adiposity as a primary outcome parameter.…”
mentioning
confidence: 99%